Pelatihan Support Sistem SD Inklusi di Era Pandemi Covid-19 - Feri Tirtoni; Rugaya Meis Andhiarini; Ika Ratna Indra Astutik (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
The purpose of implementing the community partnership program at SDN Wedi Gedangan is training in the Covid 19 pandemic support system through the use of the smart psychological test application and the design of an inclusive smart bag design to solve problems in partner schools. This is a manifestation of the Tri Dharma of higher education organized by Sidoarjo Muhammadiyah University. Some of the things that are being done are a series of activities to support the system for the inclusion program that is currently running at the school. In the first part we explain about a prototype Smart Survival Bag Inclusion which is still an initial design. The design of this bag is equipped with a barcode which has the function of helping other people in the vicinity to provide assistance if inclusive students need it, starting from the home address menu, the telephone contact menu that can be contacted, a GPS tracking device that can be installed on an Android cellphone, so that parents are not again has a heavy burden to teach their children to be independent when outside the home. The bag is also designed to have a seat that can be folded on the back of the bag. In the second session we explained the support system that can be used to carry out psychological tests on new students, both inclusion and regular through an online application during the Covid pandemic, which required everything to be systemized online, from registration to testing new students later. the application of using this application is quite easy for teachers to map students' IQs, so that potential students can be identified earlier, and this application can be accessed online and can be configured on the school's website later.